2015
DOI: 10.1007/s11136-015-1080-x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in women with lipoedema: a contextual behavioral approach

Abstract: Acceptance and Commitment Therapy with psychological flexibility as the target of change and Functional Analytic Psychotherapy with social connectedness as the target of change might be useful in treating women with lipoedema; however, further research in this area is needed. The authors conclude that psychological and biomedical interventions for women with lipoedema and their QOL merit more attention from researchers and the medical community than is currently received.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 36 publications
6
53
1
1
Order By: Relevance
“…The findings from the current study support the wealth of research literature suggesting that psychological inflexibility is related to psychological distress [33]. This provides exciting preliminary evidence about the importance of psychological flexibility in the maintenance of appearance anxiety in those with a visible difference and the findings are consistent with recently published studies which have studied single facets of psychological flexibility such as mindfulness [35] and acceptance [36]. Indeed, a recent qualitative study exploring difficulties in adjusting to appearance changes following burn injuries, found appearance concern and PTSD symptomatology might be 'intertwined', which possibly suggests that reduced psychological flexibility might form a common mechanism by which distress is PSYCHOLOGICAL FLEXIBILITY IN APPEARANCE ANXIETY maintained in both PTSD and appearance related distress in people who have experienced burn injuries [52].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The findings from the current study support the wealth of research literature suggesting that psychological inflexibility is related to psychological distress [33]. This provides exciting preliminary evidence about the importance of psychological flexibility in the maintenance of appearance anxiety in those with a visible difference and the findings are consistent with recently published studies which have studied single facets of psychological flexibility such as mindfulness [35] and acceptance [36]. Indeed, a recent qualitative study exploring difficulties in adjusting to appearance changes following burn injuries, found appearance concern and PTSD symptomatology might be 'intertwined', which possibly suggests that reduced psychological flexibility might form a common mechanism by which distress is PSYCHOLOGICAL FLEXIBILITY IN APPEARANCE ANXIETY maintained in both PTSD and appearance related distress in people who have experienced burn injuries [52].…”
Section: Discussionsupporting
confidence: 89%
“…A second study explored the role of acceptance in quality of life in those living with lipoedema. Higher levels of acceptance were reported to predict increased quality of life [36].…”
Section: Psychological Flexibility In Appearance Anxietymentioning
confidence: 99%
“…To the authors' knowledge, only one published study has examined ACT processes in relation to visible difference. Dudek, Białaszek and Ostaszewski (2016) conducted a cross-ACT FOR PEOPLE WITH VISIBLE DIFFERENCES 10 sectional survey of women affected by lipoedema, a chronic condition marked by progressive (visible) fat build-up in the lower parts of the body. They found that self-reported psychological flexibility, as measured by the Acceptance and Action Questionnaire version 2 (Bond et al, 2011), positively predicted quality of life.…”
Section: Acceptance and Commitment Therapy For This Populationmentioning
confidence: 99%
“…A third of over 100 psychological practitioners who work with people with a visible difference across Europe report using ACT to support them (Harcourt et al,2018). However, as no research other than Dudek et al's (2016) work has yet been published on ACT in this group, we will now summarize the wider literature on ACT in some of the common psychosocial problem areas for people with a visible difference. We will also introduce ACT-consistent therapeutic methods and considerations within each problem area.…”
Section: Review Of Act For the Common Problem Areasmentioning
confidence: 99%
“…Patients with lipoedema may experience similar psychological and social challenges to those faced by people with other long-term conditions. Recently published research on the psychosocial impact of lipoedema found that psychological flexibility and social connectedness were associated with higher quality of life irrespective of severity of symptoms (Dudek et al, 2016).…”
Section: Section 4: Psychosocial Support and Self-carementioning
confidence: 99%